PON3 knockout mice are susceptible to obesity, gallstone formation, and atherosclerosis. Issue 4 (4th December 2014) - Shih, Diana M.; Yu, Janet M.; Vergnes, Laurent; Dali‐Youcef, Nassim; Champion, Matthew D.; Devarajan, Asokan; Zhang, Peixiang; Castellani, Lawrence W.; Brindley, David N.; Jamey, Carole; Auwerx, Johan; Reddy, Srinivasa T.; et al.
Abstract : We report the engineering and characterization of paraoxonase‐3 knockout mice (Pon3KO). The mice were generally healthy but exhibited quantitative alterations in bile acid metabolism and a 37% increased body weight compared to the wild‐type mice on a high fat diet. PON3 was enriched in the mitochondria‐associated membrane fraction of hepatocytes. PON3 deficiency resulted in impaired mitochondrial respiration, increased mitochondrial superoxide levels, and increased hepatic expression of inflammatory genes. PON3 deficiency did not influence atherosclerosis development on an apolipoprotein E null hyperlipidemic background, but it did lead to a significant 60% increase in atherosclerotic lesion size in Pon3KO mice on the C57BL/6J background when fed a cholate‐cholesterol diet. On the diet, the Pon3KO had significantly increased plasma intermediate‐density lipoprotein/LDL cholesterol and bile acid levels. They also exhibited significantly elevated levels of hepatotoxicity markers in circulation, a 58% increase in gallstone weight, a 40% increase in hepatic cholesterol level, and increased mortality. Furthermore, Pon3KO mice exhibited decreased hepatic bile acid synthesis and decreased bile acid levels in the small intestine compared with wild‐type mice. Our study suggests a role for PON3 in the metabolism of lipid and bile acid as well as protection against atherosclerosis, gallstone disease, and obesity.—Shih, D. M., Yu, J. M., Vergnes, L., Dali‐Youcef, N., Champion, M. D., Devarajan, A., Zhang, P., Castellani, L. W., Brindley, D. N., Jamey, C. Auwerx, J., Reddy, S. T., Ford, D. A., Reue, K., Lusis, A. J. PON3 knockout mice are susceptible to obesity, gallstone formation, and atherosclerosis. FASEB J. 29, 1185‐1197 (2015). www.fasebj.org